2016
DOI: 10.1089/neu.2015.4067
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Size of Blood–Brain Barrier Opening in a Mouse Model of Blast-Induced Traumatic Brain Injury

Abstract: An increasing number of studies have reported blood-brain barrier (BBB) dysfunction after blast-induced traumatic brain injury (bTBI). Despite this evidence, there is limited quantitative understanding of the extent of BBB opening and the time course of damage after blast injury. In addition, many studies do not report kinematic parameters of head motion, making it difficult to separate contributions of primary and tertiary blast-loading. Detailed characterization of blast-induced BBB damage may hold important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 46 publications
5
37
1
Order By: Relevance
“…Consistent with previous studies, our results suggested EB fluorescence surrounding ventricle and corpus callosum may be associated with blast-induced direct vascular damage. Confocal images have shown strong widespread EB fluorescence in cortex after blast [14] and the optical density of EB in frontal cortex of blast group was over 60% higher than the sham group [11]. It was reported that focal lesions were present in many brain regions including the cortex, which were likely caused by direct shear effects induced by blast [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, our results suggested EB fluorescence surrounding ventricle and corpus callosum may be associated with blast-induced direct vascular damage. Confocal images have shown strong widespread EB fluorescence in cortex after blast [14] and the optical density of EB in frontal cortex of blast group was over 60% higher than the sham group [11]. It was reported that focal lesions were present in many brain regions including the cortex, which were likely caused by direct shear effects induced by blast [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Breakdown of the BBB after blast exposure is commonly reported (Elder et al, 2015; Kabu et al, 2015; Readnower et al, 2010; Shetty et al, 2014; Yeoh et al, 2013). We recently found significant changes in BBB integrity following primary blast loading in vitro and in vivo (Hue et al, 2014; Hue et al, 2013; Hue et al, 2015). Unlike the in vitro preparations, even a very small compromise of the blood-brain barrier could lead to serum components leaking into the extracellular space and triggering a strong gliotic response.…”
Section: Discussionmentioning
confidence: 99%
“…1B, C) designed with past work as reference: 1) mild blast - peak incident overpressure of 215 ± 13 kPa, duration of 0.65 ± 0.04 ms, and an impulse of 46 ± 5 kPa * ms, which is within the range of conditions causing cognitive impairment in rodents following blast exposure (Kovacs et al, 2014), and 2) moderate blast - peak incident overpressure of 415 ± 41 kPa, duration of 1.04 ± 0.04 ms, and impulse of 148 ± 12 kPa * ms, which is above the threshold for changes in BBB permeability in vitro (Hue et al, 2013; Hue et al, 2015) and LTP deficits in organotypic slice cultures (Effgen et al, 2014; Vogel et al, 2015). This range of blast loading is comparable to exposure to a 105-mm artillery round at a standoff distance of 5–10 m. The effects of unconstrained motion were only examined at the lower exposure level, as the higher exposure resulted in significant mortality.…”
Section: Methodsmentioning
confidence: 96%
“…We did see BBB damage 24 h post LFPI, demonstrated by the immunohistochemical staining of mouse IgG at the injury site; additionally, a loss of BBB integrity using the bTBI model occurring within the 24 h post injury has been previously well established 23, 39. There was no visible disruption of the brain architecture at 24 days post blast injury.…”
Section: Discussionmentioning
confidence: 52%
“…There was no visible disruption of the brain architecture at 24 days post blast injury. It has been well documented that the integrity of BBB is reestablished 24 h post blast injury,23, 39but we wanted to verify that overt tissue disruption did not occur. Damage to the BBB in both of these models leads to the loss of the brain's normal immunologic privilege and isolation from the systemic immune system.…”
Section: Discussionmentioning
confidence: 99%